Gender Stereotypes Portrayed in a Senior High School English Textbook Published by Indonesia Ministry of Education and Culture - Habib, Fazl Ahmad; Wija Putra, Bambang Arya; Setyono, Budi (Jurnal Edukasi, 2020)
The study was conducted to elaborate the gender stereotypes in a national senior high school English textbook in Indonesia. The qualitative study is applied and Critical Discourse Analysis is used as the preferable approach. This research provides the development of Mullet’s (2018) CDA generic framework analysis which based on Fairclough’s (2001) model. The result of the study divulged various gender stereotypes portrayed such as gender firstness, equality, dominance and bias. Many biased stereotypes are found on how the female character being portrayed in leadership matter, social relation, and family. In contrast, in the matter of physical traits, male characters are portrayed to have more and various interests in sports. The gender stereotypes portrayed in both textual and visual contents within the textbook. Many illustrations portrayed women stereotypically biased so do the textual materials such as narrative text, recount text/biography, transactional text, and descriptive text. Somehow, it is suggested that the authors should consider the position and the portrayal of gender stereotypes as problematic as proven by many previous studies. Keywords: Critical Discourse Analysis, Fairclough Model, Gender Stereotypes, Textbook.